2020
DOI: 10.21203/rs.3.rs-44925/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosomal painting of the sandpiper (Actitis macularius) detects several fissions for the Scolopacidae family (Charadriiformes)

Abstract: Background: The Scolopacidae family (Suborder Scolopaci, Charadriiformes) is composed of sandpipers and snipes; these birds are long-distance migrants that show great diversity in their behavior and habitat use. Cytogenetic studies in the Scolopacidae family show the highest diploid numbers for order Charadriiformes. This work analyzes for the first time the karyotype of Actitis macularius by classic cytogenetics and chromosome painting. Results: The species has a diploid number of 92, composed mostly of teloc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…While early comparisons of avian genomes were restricted to the chicken and zebra finch, where high level comparisons of synteny and karyotype led to the conclusion that bird genomes were largely stable compared to mammals (Ellegren 2010), the discovery of many intrachromosomal rearrangements across birds (Hooper and Price 2017;Skinner and Griffin 2012;Zhang et al 2014;Farre et al 2016) and interchromosomal recombination in falcons, parrots and sandpipers (O'Connor et al 2018;Coelho et al 2019;Pinheiro et al 2021) has shown that at a finer resolution for comparison, the avian genome is rather dynamic. The highly variable rate of TE expansion we have observed across birds extends knowledge from avian orders with "unusual" repeat landscapes, i.e., Piciformes (Manthey et al 2018) and Passeriformes (Warren et al 2010), and provides further evidence that the genome evolution of bird orders and species within orders differs significantly, even though synteny is often conserved.…”
Section: Conclusion: the Avian Genome Is More Dynamic Than Meets The Eyementioning
confidence: 99%
“…While early comparisons of avian genomes were restricted to the chicken and zebra finch, where high level comparisons of synteny and karyotype led to the conclusion that bird genomes were largely stable compared to mammals (Ellegren 2010), the discovery of many intrachromosomal rearrangements across birds (Hooper and Price 2017;Skinner and Griffin 2012;Zhang et al 2014;Farre et al 2016) and interchromosomal recombination in falcons, parrots and sandpipers (O'Connor et al 2018;Coelho et al 2019;Pinheiro et al 2021) has shown that at a finer resolution for comparison, the avian genome is rather dynamic. The highly variable rate of TE expansion we have observed across birds extends knowledge from avian orders with "unusual" repeat landscapes, i.e., Piciformes (Manthey et al 2018) and Passeriformes (Warren et al 2010), and provides further evidence that the genome evolution of bird orders and species within orders differs significantly, even though synteny is often conserved.…”
Section: Conclusion: the Avian Genome Is More Dynamic Than Meets The Eyementioning
confidence: 99%